"Filthy rich" and "dirt poor:" social and cultural dimensions of solid waste management (SWM) in Lagos. (2nd January 2018) - Olukoju, Ayodeji
Abstract: This paper analyses how household solid waste was perceived and handled in traditional Yoruba and contemporary Lagos society in South West Nigeria. It highlights the roles of individuals, households, changing lifestyles and diet, business cycles, residential segregation, and state and non-state actors and institutions in waste management in Lagos. The filthy rich/dirt poor divide in Lagos is epitomised by spatial segregation and social stratification, reflected by contrasting highbrow neighbourhoods and massive dumpsites in the metropolis. Central to this discussion are changing economic dynamics. The boom years were characterised by conspicuous consumption, waste and replacement while economic adversity precipitated destitution, re-use and recycling of waste, and recourse to imported second-hand clothing and household utensils. The paper recommends a multi-pronged sustainable waste management strategy for Lagos.